Perception of Millennials towards Eco-Friendly Products in Kathmandu Valley - Sedhai, Pratigya; Khatri, Sohan Babu (Journal of Business and Social Sciences Research, 2023)
This study aims to analyse the effect of various influencing factors on the perception of millennials towards eco-friendly products in Kathmandu Valley. The study is quantitative and descriptive and conducted using primary sources of data. It has adopted the mono-method, whereby survey and statement type questions have been used to analyse quantitative data. A non-probabilistic sampling technique has been used in this research with a sample size of 384. The collected data were analysed using descriptive statistics, independent sample t-test, one-way ANOVA test, correlation analysis, reliability testing, and regression analysis. The influencing variables considered are interest in the protection of the environment, reusability, consumer Greendex/ green attitude, concern for health, subjective norms and social influence, trust in green product, perceived quality of green product and environmental advertising. The results show that there is a positive correlation between all the influencing factors and millennials’ perception towards eco-friendly products. Environmental advertising has created the highest impact on the millennials’ perception by analysing the beta coefficient. Overall, the finding suggests that the concerned authorities, policymakers, producers/manufacturers and marketers of eco-friendly products should focus more on promoting the products using environmental claims, attributes, structures, rules, and tactics so that millennials’ perception towards green purchase can be positively influenced.